Ultrafast scalable parallel algorithm for the radial distribution function histogramming using MPI maps - Kouetcha, Daniella Nguemalieu; Ramézani, Hamidréza; Cohaut, Nathalie (The Journal of supercomputing, 2017)
In the present paper, an ultrafast and scalable parallel program for the Radial Pair Function (RPF) is presented via pure Message Passing Interface (MPI) paradigm. The parallel code computes the radial distribution function for the single-component as well as multi-component systems. The single-component and multi-component systems have been extracted for benchmarking purposes by means of user-written codes in C++ for the Graphite structure and MPI C++ for hydrogen adsorption via Grand Canonical Monte Carlo (GCMC) in the Single-Walled Carbon Nanotube (SWNT), respectively. The speedup and efficiency curves substantiate an excellent performance in terms of computing time and computation size as well. Additionally, the mentioned MPI paradigms are nearly five times (single-component systems) and two times (multi-component systems) faster than the relevant parallel codes using a machine with 48 CPUs and NVIDIA Quadro K5200/PCIe/SSE2. Some conclusions and outlooks pertaining to the numerical implementations, algorithm optimization involving the space decomposition idea have been discussed and provided.